2019
DOI: 10.17236/sat00194
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral peromelia of the left pelvic limb in a Brown Swiss calf

Abstract: Unilateral peromelia of the left pelvic limb in a Brown Swiss calfCongenital deformities of the limbs occur sporadically in various species, but the cause is often unclear. The clinically healthy female Brown Swiss calf presented here showed a congenital peromelia of the left hind limb. The affected limb is twisted, disproportional and the bones distally of the metatarsus are missing. Karyotyping and genome sequencing did not indicate on a genetic cause of the anomaly. An infection with the Schmallenberg virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Unfortunately, the true frequency of limb malformations in cattle is unknown and not well recorded due to lack of surveillance programs. However, there are several scientific reports about bovine limb malformations from as early as the 1920s (Table 1) [2,[36][37][38][39][40]. Those studies have reported that affected calves had limb defects distal of the knee and elbow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the true frequency of limb malformations in cattle is unknown and not well recorded due to lack of surveillance programs. However, there are several scientific reports about bovine limb malformations from as early as the 1920s (Table 1) [2,[36][37][38][39][40]. Those studies have reported that affected calves had limb defects distal of the knee and elbow.…”
Section: Discussionmentioning
confidence: 99%
“…Different forms of dysmelia are distinguished depending on the number of affected limbs and the part of the limb that is malformed or missing [1]. Various limb malformation phenotypes ranging from deficiencies of the upper and lower limb have been described in humans and various animal species (Table 1) [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%